Influence of seed treatment with biocides and foliar spray with fungicides for management of brown leaf spot and sheath blight of paddy - and RAMESH SINGH, S.K. BISWAS*, VED RATAN, S.S.L. SRIVASTA (Indian Phytopathology, 2008)
Bio-agents like Trichoderma harzianum, T. viride , bioformulation of Pseudomonas fluorescense and T. harzianum and botanical like garlic extract and Achook were tested against brown spot and sheath blight pathogens in vitro and also as seed dresser. In dual culture test T. harzianum and its bioformulation reduced mycelial growth by 55.3% 58.1% in D. oryzae and 42.7 % 43.0% in Rhizoctonia solani respectively. Seed treatment with biocides was provided good protection of seed against seed borne infection, resulted enhanced germination of paddy seed. The maximum 92% germination was recorded in seed treatment with bioformulation of T. harzianum followed by spore suspension of T. harzianum (89.3 %). The enhanced growth of paddy seedling has also been recorded as a result of the effect of seed treatment with biocides. The increase of 21.6 and 21.Q percent of shoot length and 25.8 and 25.1 of root length over control was recorded in seed treatment with bioformulation of T. harzianum and P. fluorescense respectively.